Pengaruh Model PBL Terhadap Pemahaman Konsep IPA Peserta Didik UPTD SPF SDN 8 Maccope - Muslimin; Nurul Mukhlisa; Sahra Ramadhani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research objectives to determine students' understanding concept science energy transformation material before and after implementing PBL mode and influence the PBL model on understanding concept science of energy transformation material UPTD SPF students at SD Negeri 8 Maccope.The research is type experimental with a quantitative approach.The independent variable is application PBL,while dependent variable is understanding concepts science.The population in this research is all grade IV students..Data collection techniques use tests.The data analysis techniques used descriptive statistics and infer           ential statistics.The descriptive research results showed grade IV students' understanding of science concepts before PBL model was applied was in the poor category,while class IV students' understanding of science concepts after PBL model was applied was in the very good category.The results of the inferential research show that the hypothesis test obtained a significance value of 0.000 < 0.05 so that H1 was accepted,meaning that there was difference in the average science learning outcomes in energy transformation material for class IV UPTD SPF students at SD Negeri 8 Maccope between before and after implementation of PBL model.Conclusion that there is influence of the application of the PBL model on the understanding of science concepts in energy transformation material for grade IV students.